THE IMPLEMENTATION OF ONLINE LEARNING IN RURAL AREAS DURING COVID-19: VOICE OF RURAL ENGLISH TEACHERS - Maria Olga Jelimun; Yosefina Heleonora Jem; Indra Susanto; Yanuarius Mardiantoro (Premise: Journal of English Education and Applied Linguistics, 2022)
This research investigates the rural teachers' voices related to implementing online learning during covid-19. Due to understanding the schools' readiness in remote areas, it is essential to carry out English learning activities in emergencies. The subject of this research was 6 English teachers from two schools. Three were from SMAN 1 Ruteng-Anam, and three other teachers from SMAN 1 Lelak Manggarai regency, Nusa Tenggara-Timur. This research is categorized as qualitative research. The data were explained descriptively. In collecting the data, a questionnaire and interview were used. The questionnaire consisted of 3 main questionsinvolved. They covered the teachers' enthusiasm for Teaching English Using  Technology, the Implementation of Online Learning During the COVID-19 Epidemic, and the obstacles that English teachers faced during the pandemic. The teachers' additional information was gathered in the interview section. The data were analyzed and explained descriptively based on the result of the questionnaires and interviews. The result of the research showed that teachers at SMAN 1 Ruteng Anam and SMAN 1 Lelak during the pandemic still adapted to the situation. The limitations of technological facilities during the pandemic are not able to prevent teachers from teaching English activities. However, English teachers experienced many issues during the pandemic. The issues are related to teaching planning, delivery, and evaluation of the material. Those problems implicated the quality and intensity of learning activity, in which many English teachers assessed the students' improvement subjectively.